Bioactive Cyclopeptide Alkaloids and Ceanothane Triterpenoids from Ziziphus mauritiana Roots: Antiplasmodial Activity, UHPLC-MS/MS Molecular Networking, ADMET Profiling, and Target Prediction - Sylvestre Saidou Tsila; Mc Jesus Kinyok; Joseph Eric Mbasso Tameko; Bel Youssouf G. Mountessou; Kevine Johanne Jumeta Dongmo; Jean Koffi Garba; Noella Molisa Efange; Lawrence Ayong; Yannick Stéphane Fotsing Fongang; Jean Jules Kezetas Bankeu; Norbert Sewald; Bruno Ndjakou Lenta (Molecules)
Malaria continues to pose a significant global health burden, driving the search for novel antimalarial agents to address emerging drug resistance. This study evaluated the antiplasmodial potential of Ziziphus mauritiana Lam. (Rhamnaceae) roots through an integrated phytochemical and pharmacological approach. The ethanol extract, along with its derived fractions, demonstrated potent in vitro activity against the chloroquine-sensitive Plasmodium falciparum strain 3D7 (Pf3D7), with the ethyl acetate-soluble (IC50 = 11.35 µg/mL) and alkaloid-rich (IC50 = 4.75 µg/mL) fractions showing particularly strong inhibition. UHPLC-DAD-ESI-QTOF-MS/MS-based molecular networking enabled the identification of thirty-two secondary metabolites (1–32), comprising twenty-five cyclopeptide alkaloids (CPAs), five of which had not yet been described (11, 20, 22, 23, 25), and seven known triterpenoids. Bioactivity-guided isolation yielded thirteen purified compounds (5, 6, 14, 26–30, 32–36), with betulinic acid (30; IC50 = 19.0 µM) and zizyberenalic acid (32; IC50 = 20.45 µM) exhibiting the most potent antiplasmodial effects. Computational ADMET analysis identified mauritine F (4), hemisine A (10), and nummularine R (21) as particularly promising lead compounds, demonstrating favourable pharmacokinetic properties, low toxicity profiles, and predicted activity against both family A G protein-coupled receptors and evolutionarily distinct Plasmodium protein kinases. Quantitative analysis revealed exceptionally high concentrations of key bioactive constituents, notably zizyberenalic acid (24.3 mg/g) in the root extracts. These findings provide robust scientific validation for the traditional use of Z. mauritiana in malaria treatment while identifying specific cyclopeptide alkaloids and triterpenoids as valuable scaffolds for antimalarial drug development. The study highlights the effectiveness of combining advanced metabolomics, bioassay-guided fractionation, and computational pharmacology in natural product-based drug discovery against resistant malaria strains.